2022
DOI: 10.1667/rade-21-00237.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transgenic NSG-SGM3 Mouse Model of Precision Radiation-Induced Chronic Hyposalivation

Abstract: Regenerative medicine holds promise to cure radiation-induced salivary hypofunction, a chronic side effect in patients with head and neck cancers, therefore reliable preclinical models for salivary regenerative outcome will promote progress towards therapies. In this study, our objective was to develop a cone beam computed tomography-guided precision ionizing radiation-induced preclinical model of chronic hyposalivation using immunodeficient NSG-SGM3 mice. Using a Schirmer's test based sialagogue-stimulated sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Studies in mice have shown that after irradiation injury, the salivary gland tissue goes through an initial regenerative phase, which ultimately fails in the long term ( 58 60 ), mirroring what occurs in humans after radiotherapy ( 41 , 61 , 62 ). We therefore extended our studies to examine the roles of macrophages in the initial regenerative phase by determining the effects of macrophage depletion up to the point at which many indices of damage and inflammation have subsided and repair is under way (day 28) ( 39 , 60 , 63 , 64 ). To this end, we administered DTx every other day from day 17 to day 27, undertook saliva measurements at day 27, and analyzed the SMG at day 28.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mice have shown that after irradiation injury, the salivary gland tissue goes through an initial regenerative phase, which ultimately fails in the long term ( 58 60 ), mirroring what occurs in humans after radiotherapy ( 41 , 61 , 62 ). We therefore extended our studies to examine the roles of macrophages in the initial regenerative phase by determining the effects of macrophage depletion up to the point at which many indices of damage and inflammation have subsided and repair is under way (day 28) ( 39 , 60 , 63 , 64 ). To this end, we administered DTx every other day from day 17 to day 27, undertook saliva measurements at day 27, and analyzed the SMG at day 28.…”
Section: Resultsmentioning
confidence: 99%
“…Organoids were then stained as previously described 6 with primary and secondary antibodies described in Supplementary Table S3 . Nuclei were counterstained with DAPI Fluoromount-G® (Southern Biotech, Birmingham, AL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Conditions like diabetes, viral infections (mumps, HIV, hepatitis), aging, trauma, surgery-related nerve damage, dehydration, and salivary gland tumors can also contribute to a decline in salivary function, leading to dry mouth. Despite decades of research in salivary gland function using animal models 6 , a curative treatment for salivary dysfunction remains elusive 7 .…”
Section: Introductionmentioning
confidence: 99%